2013
DOI: 10.1111/petr.12116
|View full text |Cite
|
Sign up to set email alerts
|

The use of transient elastography and non‐invasive serum markers of fibrosis in pediatric liver transplant recipients

Abstract: The use of non-invasive markers to diagnose liver allograft fibrosis is not well established in children after LTx. TE, FT, and ELF score were performed in 117 liver-transplanted children (60M, 8.9 [0.5-18.5] yr) and 336 healthy controls. Liver biopsy was available in 36 children. Results of histology and non-invasive markers were compared using correlation coefficient or Mann-Whitney U-test as appropriate. TE correlated best with histological degree of fibrosis (r = 0.85 vs. r = 0.04 [FT] or r = -0.38 [ELF]).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 37 publications
3
42
1
2
Order By: Relevance
“…According to standard protocol, LSM was only considered acceptable if all three of the following conditions were met: At least ten valid shots were obtained, the success rate of at least 10 valid shots had to be >60%, and the ratio of the median of 10 valid shots and the IQR was <30%. LSM ≥ 7.5 kPa was considered abnormal and suggestive of allograft fibrosis, as described by a previous study …”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…According to standard protocol, LSM was only considered acceptable if all three of the following conditions were met: At least ten valid shots were obtained, the success rate of at least 10 valid shots had to be >60%, and the ratio of the median of 10 valid shots and the IQR was <30%. LSM ≥ 7.5 kPa was considered abnormal and suggestive of allograft fibrosis, as described by a previous study …”
Section: Methodsmentioning
confidence: 75%
“…Moreover, a distorted anatomy may also increase the difficulty in performing TE, as well as the presence of scar tissue. Similarly, Goldschmidt et al showed that the heterogenous result of LSM in transplanted children without fibrosis (F0) ranged from 5.4 to 20.4 kPa with the median cutoff value of 7.55 kPa. We used the cutoff value of 7.55 kPa according to this report.…”
Section: Discussionmentioning
confidence: 99%
“…Two pediatric studies comparing TE to histology after transplant have confirmed the potential of the technique, but only 50 patients have been studied. The technique is more difficult in split or reduced grafts …”
Section: Detection Of Late Allograft Hepatitis and Fibrosismentioning
confidence: 99%
“…The use of TE to assess liver stiffness measurement has now become widely available for the diagnosis of liver fibrosis as a rapid, noninvasive test, especially in patients with chronic viral hepatitis C, those with nonalcoholic liver disease, 35 and liver transplant patients 36 , 37 . A recent meta‐analysis that included 22 studies showed that the pooled estimates for significant fibrosis (≥F2) measured 7.71 kPa (LSM cutoff value) with a sensitivity of 71.9% and a specificity of 82.4%, whereas for cirrhosis (F4), the results showed a cutoff of 15.08 kPa with a sensitivity of 84.5% and a specificity of 94.7% 38 …”
Section: Discussionmentioning
confidence: 99%